Finding balance 2019 benchmarking the performance of state owned banks in the Pacific. (Metro Manila, Philippines Asian Development Bank, 2019)
A key finding is the considerable business financing gap in the region, particularly for small-medium enterprises and sectors such as agriculture and fisheries. The report suggests that state owned banks could address this demand, but would need to do so on commercial terms and without distorting local markets. These institutions would need to strengthen their balance sheets and risk assessment practices and operate under the same market disciplines as private banks.
Keywords: Financial institution; Service industries; Electronic books